The prevalence of HBV, HTLV, HIV and concurrent infections in blood recipients of the South African National Blood Service (SANBS) - Willemse, Reynier (Vaal University of Technology, 2020)
Background: Currently, the South African National Blood Services are not testing for HTLV and HTLV screening is not mandated by the WHO or by regulatory standards in South Africa. Looking at the uniquely high prevalence of HIV and HIV / HBV co-infections in the South African population and taking into account the literature that suggests that most of these infected patients will be receiving blood, exposing these patients to an additional burden like HTLV can result in an increased disease progression of HIV to AIDS and a poor prognosis in these infected patients. Study design and methods: A blinded cross-sectional study was performed. 7015 specimens were collected from all blood transfusion laboratories across South Africa excluding the Western Cape Blood Transfusion Service laboratories. The specimens collected were tested using the ABBOTT Alinity S® Immunochemiluminescent autoanalyser. All test results were confirmed with the Roche Cobas® E801 and E411 auto analyser. Results: Over all prevalence for HIV was 39.39% (N=2763), HBV 7.57% (n=531) and HTLV 0.70% (N=49). Concurrent infection for HIV/HBV 4.92% (N=345), HIV/HTLV 0.36% (N=25), HBV/HTLV 0.09% (N=6) and HIV/HBV/HTLV 0.07% (N=5). Conclusion: This study confirmed an overall high prevalence of HIV and HBV infections among patients receiving blood products from the SANBS. Compared to the general population, the HIV prevalence in blood recipients was two-fold higher. Patients receiving a blood transfusion from the SANBS have high rates of HIV, HBV and HTLV which should be taken into consideration when determining donor screening strategies.
M. Tech. (Department of Biotechnology, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: South African National Blood Services; Human T-lymphotropic virus (HTLV); HTLV screening; World Health Organization (WHO); Human immunodeficiency virus (HIV); Hepatitis B (HBV); Acquired immunodeficiency syndrome (AIDS); Dissertations, Academic -- South Africa.; HIV infections -- South Africa.; AIDS (Disease); Hepatitis B virus.; HTLV (Viruses); Blood -- Transfusion -- Complications.